(untitled) (Research, Society and Development, 2021)
The present work, with the objective of visualizing the principle of cooperation and its non-procedural scope, observed that the Code of Civil Procedure of 2015, emerges as an important postulate of judicial effectiveness, guiding the relations of two procedural subjects. It is a qualitative bibliographic research, tracing the principle of cooperation from a different perspective than the one usually found, this article emphasizes the fundamental role of the non-cooperative process, and not subject to the parties (plaintiff and defendant), since two magistrates cooperate, there is a possibility that decisions on the merits do not respect their real purpose. On the other hand, the importance of fungibility / adequacy of the context is also outlined, in order to conclude that there has not been an adequate, fair and just process, there is cooperation between the parties involved, non-litigation, and two procedural matters - individual matters, including the parties, defendants, judges, servants, experts, interpreters and also interested third parties.